1972
DOI: 10.1139/v72-112
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron Spectra of Phosgene and Thiophosgene

Abstract: The high resolution photoelectron spectra of phosgene and thiophosgene have been obtained and, in each case, all ionization potentials up to 21.2 eV determined. The spectra are interpreted in terms of the molecular orbital structures and it is concluded that there is a strong interaction between the chlorine p, "lone pair" electrons and those in the C=O or C=S 71 bond. The measured ionization potentials are compared with those calculated by the CNDO/2 method and with those obtained for similar molecules.On a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…Extended Hiickel calculations on the chloroethylenes (13) predict strong mixing of the a" orbitals. Similar large mixing of n: orbitals has been concluded for Cl,C--0 and C1,C-S (20). Klasson and Manne (13) have suggested that there is only one i.p.…”
Section: Vinyl Bromidesupporting
confidence: 73%
See 1 more Smart Citation
“…Extended Hiickel calculations on the chloroethylenes (13) predict strong mixing of the a" orbitals. Similar large mixing of n: orbitals has been concluded for Cl,C--0 and C1,C-S (20). Klasson and Manne (13) have suggested that there is only one i.p.…”
Section: Vinyl Bromidesupporting
confidence: 73%
“…The order is that expected on the basis of brominebromine overlap only, with the a, combination occurring at the highest binding energy. The importance of the interaction of these "lone pair" orbitals with other molecular orbitals in modifying the above ordering has been pointed out for dichloro-and dibromomethane (24), dichlorosilane (25), and other dichloro compounds (20,26). The a, orbital is symmetry determined and cannot interact with any other valence molecular orbital.…”
Section: Cis-12-dibromoethylenementioning
confidence: 99%
“…The measured spectrum between 9 and 20 eV is shown in figure 2. I t agrees with minor differences from th a t found by Chadwick (1972).…”
Section: (B) Thiocarbonyl Chloridesupporting
confidence: 88%
“…17 The electron configuration of the general state has been determined by photoelectron spectroscopy to be ͓core͔ (9a 1 ) 2 (10a 1 ) 2 (6b 2 ) 2 (11a 1 ) 2 (7b 2 ) 2 (3b 1 ) 2 (12a 1 ) 2 ϫ(2a 2 ) 2 (8b 2 ) 2 (13a 1 ) 2 (4b 1 ) 2 (9b 2 ) 2 , where the 9a 1 , 6b 2 , and 10a 1 molecular orbitals ͑MOs͒ contain the bonding electrons, the 3b 1 and the 4b 1 orbitals are a combination of the bonding electrons and Cl(3p) electrons, and the 9b 2 and 13a 1 MOs contain the sulfur lone pair electrons. 18 The thiophosgene absorption spectrum as shown in Fig. 1 was reported by Farnworth and King.…”
Section: Introductionmentioning
confidence: 67%